Optimalisasi Sirkular Ekonomi melalui Implementasi SIMBAHNIRA dalam Manajemen Limbah Organik di Desa Tanjung - Maliana Puspa Arum; Chusnul Maulidina Hidayat; Paradise Paradise (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2025)
Waste issues are the main focus and challenge in supporting sustainable development and the implementation of circular economy principles. This community service aims to optimize the implementation of a circular economy system through the use of SIMBAHNIRA (Organic Waste Management Information System) technology in managing organic waste at KSM Brayan, Tanjung Village. The methods used in this service are socialization, training, and direct assistance to KSM Brayan members. Data were collected through observation, interviews, and documentation in the SIMBAHNIRA implementation process. The results show that the implementation of SIMBAHNIRA has succeeded in increasing the efficiency of waste transaction recording, encouraging community participation in collecting organic waste.